Hubungan antara Loneliness dengan Tindakan Self-Harm pada Siswa SMP di Kota Padang - Fadilla, Suci; Ardi, Zadrian (MASALIQ, 2024)
This research was motivated by the discovery that self-harm was a very urgent phenomenon among teenagers. Many factors influence someone to do self-harm, one of which is loneliness. Further research was conducted regarding the relationship between loneliness and self-harm in junior high school students. The aims of this research are: (1) to describe the level of loneliness; (2) describe self-harm actions towards students; (3) examine the relationship between loneliness and self-harm in junior high school students in the city of Padang. This research uses quantitative methods with a descriptive approach. The sample in this research was 35 junior high school students in Padang City who were selected using purposive sampling technique. Data were obtained using loneliness instruments and the SHI-Indonesian version which are valid and reliable. Data processing is carried out using the product moment correlation formula. The results of the research show that loneliness in junior high school X students is in the moderate category (46.88%), self-harm actions in junior high school.